Utilization of Adequately Iodized Salt and its Barriers Among Sub-Urban Households of Chengalpattu District- Tamil Nadu - Siddharthan Athiyaman; Virudhunagar Muthuprakash Anantha Eashwar; Hariharan Surathkumaar; Umadevi Ramachandran (Journal of Epidemiology and Public Health, 2024)
Background: Iodine is a crucial nutrient humans need for healthy mental and physical development. Iodine deficiency disorder (IDD) continues to pose a real threat to public health across several nations, including India. This study aimed to estimate the prevalence of the use of adequately iodized salt and to determine the barriers to the use of adequately iodized salt among suburban households.Subjects and Method: A Community-based cross-sectional study was done among 250 sub-urban households using a multistage sampling technique in Chengalpattu district, Tamil Nadu. The study was carried out between the period of July to November 2023. Data was collected by both standardized and pre-tested semi-structured questionnaires. The iodine content of salt was assessed by an MBI spot testing kit. The dependent variable was adequately iodized salt and the independent variable was sociodemographic details and variables related to the utilization of iodized salt. Data were analyzed using SPSS version 25.Results: The prevalence of utilization of adequately iodized salt was 76.8 % and barriers to the use of adequately iodized salt among sub-urban households were, using a wet spoon/hand to take salt from the container, container of the salt kept open / both ways, storing salt in the steel container and storing in the original salt pocket itself.Conclusion: Specific education regarding proper storage, handling, duration, and the importance of iodized salt needs to be implemented to increase community awareness and to focus on behavior change communication to bring a positive attitude toward the utilization of iodized salt.